PRODUKSI JENIS KELAMIN TANDAN BUNGA KELAPA SAWIT DAN RESPONSNYA TERHADAP PERLAKUAN EXOGENOUS HORMONE TANAMAN PADA LAHAN YANG MENGALAMI KEKERINGAN - Iman Yani Harahap; Sumaryanto Sumaryanto; Taufiq Caesar Hidayat; Wan Rizki Fauzi; Yusran Pangaribuan (Pusat Penelitian Kelapa Sawit, 2017)
To determining effects of drought on the oil palm sex inflorescene and its response on plant hormone treatmet under drought condition. Then it was carried out the serial treatment at indonesian oil palm research institute (IOPRI) field area trial in Pulau Maria, Asahan District, North Sumatra during 4 year (2013 until midle of 2016). These area having flat topography class with sandy loam texture of typic paleudult soil type and suffering frequently of 200- 460 mm water deficit per year. The trial were undertaken on oil palm tenera's type with 8 years old (planted in 2005). The trial including, 4 kind of phytohormone plus the control treatment, which treated on plant with several of dose and frequency. The phytohormone were IAA (auxsin, Indole-3-acetic acid), BAP (citokinin, 6-benzylaminopurine), GA_3 (gibberelline, gibberellic acid), dan ABA (absisic acid). The dose of each of these kind of hormone were 100, 300, dan 500 ppm, with frequenscy application once and twice per year. The trial design following randomized block design with 3 replicated. Individual unit treatment was the indivduplant. The variable that observed were female, male, and aborted inflorescence; number of frond production; and vegetative growth (height of plant and length of rachis frond). Analysis effect the drought on oil palm sex inflorescene were done by correlation analysis between rainfall and water deficit with inflorescene production. The result shown drought period decline of female inflorescense, and increasing male and aborted inflorescense. Auxin (IAA) treatment, induced vegetatif growth, but contrarily, declining female inflorescense production and increasing male and aborted inflorescense. Gibberelline (GA_3) treatment, decreasing commonly female inflorescense production, and increasing male and aborted inflorescense, mainly in the certain peak of drought periods. Citokinin (ABA) and absicic asid (ABA), tend tokeep female inflorescense production in drought condition, in a way reducing number of aborted inflorescense. Citokinin (BAP), was dominantly plant hormone to keep female inflorescense production.